Language play in the narrative writing of 9–11-year-olds. Issue 5 (29th July 2018) - Burrell, Andrew; Beard, Roger
ABSTRACT: There has been little research into 'language play', the manipulation of language for enjoyment, in children's narrative writing. The unprompted language play of 36 children was investigated in their writing of an imaginative story. The sample comprised three attainment sub-groups from a larger repeat-design quantitative study of writing development in the 9–11 age range. A total of 71 stories were further analysed, using qualitative methods derived from the relevant literature. Extensive use of language play was evident, as well as some stylistic differences between the sub-groups. The findings suggest that children's propensity for manipulating the forms, meanings and uses of language might be channelled more explicitly into the teaching and learning of writing.